Lie algebras associated with quadratic forms and their applications to Ringel-Hall algebras - Kosakowska, J. (Algebra and Discrete Mathematics, 2008)
We define and investigate Lie algebras associated with quadratic forms. We also present their connections with Lie algebras and Ringel-Hall algebras associated with representation directed algebras.